Lecturers' Facilitation Strategies in Group Presentations in Language Classrooms in Higher Education: Rhetorical Pattern Analysis - Jasrial, Dedi (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
Studies on teaching strategies in language learning have been extensively conducted by scholars to facilitate classroom interaction and active learning activities, especially group presentations. However, studies on lecturers' facilitation strategies are rarely found in the literature. This research aims to investigate the rhetorical patterns in lecturers' facilitation strategies in group presentations in language classrooms in higher education. This discourse analysis study used a qualitative approach conducted over two semesters. Data were gathered through participant observation. The data were analyzed qualitatively using the rhetorical step technique. The results show that language lecturers employed three facilitation strategies in group presentations in language classrooms: GQTR (Group Presentation-Question and Answer-Lecturer’s Reinforcement), GCAPQLR (Group Presentation-Comments and Additions-Presenters Response-Question and Answer-Lecturer’s Reinforcement), dan GCCARQLR (Group Presentation-Contributor-Comments and Addition-Response-Questions-Lecturer’s Reinforcement). The study concludes that these facilitation strategies are crucial for fostering a dynamic learning environment, promoting active engagement, and enhancing interaction among students. The pedagogical implications suggest that language instructors can improve classroom interaction and active learning by implementing these strategies, which can also help develop students' speaking, listening, and analytical skills during group presentations.